Illustration d’une Approche de Prospective Stratégique/Elaboration de Scénarios pour la Sécurité Alimentaire et l’Agroécologie en Tunisie - Sghaier, Mongi; Frija, Aymen; Darghouth, Mohamed Aziz (International Center for Agricultural Research in the Dry Areas, 2024)
The objective of this presentation is to disseminate insights, methodologies, and state-of-the-art knowledge regarding the efficacy of strategic foresight approaches in the context of scenario development in food security studies. The presentation synthesizes contemporary and recent studies on the foresight of agri-food systems and food security on a global scale, with a particular focus on Tunisia. Additionally, it sheds light on the scenario development methodology for the future of agri-food systems in Tunisia, with the aim of formulating robust food security strategies.